Student resource exchange: a web-based system for sharing educational resources among students - Saw, Hui Loo (2025)
This project focuses on the development of the Student Resource Exchange, a web-based platform designed to enhance the sharing and accessibility of educational resources among students. The platform addresses key limitations found in existing resource-sharing platforms, such as the lack of automated content analysis, insufficient content classification, and inadequate support for personalized learning. To overcome these issues, the system integrates Optical Character Recognition (OCR) for extracting text from images, Whisper for video transcription, and Google Gemini for generating concise video summaries. Natural Language Processing (NLP) techniques, such as TF-IDF with Logistic Regression for hate speech detection and BERT-based sentiment analysis, ensure safe and meaningful interaction within the platform. For content classification, the Google Gemini API with structured prompt engineering is applied to automatically organize materials into relevant academic courses. In addition, the platform introduces AI-powered study tools, including automated question generation and flashcards, as well as a built-in smart calendar planner that applies conflict detection and priority-based scheduling algorithms to help students manage study sessions and deadlines effectively. This system aims to provide a more efficient, user-friendly, and engaging platform for students to exchange educational resources, ultimately fostering a more collaborative and accessible learning environment.